PENGARUH KOMITMEN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. AGUNG PAPER KLUNGKUNG - Ni Luh Putu Eka Anggraningsih; Pande Ketut Ribek; Tiksnayana Vipraprastha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
This research aims to analyze the influence of work commitment, work motivation, and work environment on employee performance at CV. Agung Paper Klungkung. The research sample involves 38 employees from the company. Data collection methods were conducted through observation, interviews, and documentation. The results of data analysis indicate that work commitment has a positive and significant influence on employee performance, work motivation has a positive and significant influence on employee performance. On the other hand, the work environment also has a positive and significant influence on employee performance. These findings provide insights for the company regarding factors that can affect employee performance, thereby enhancing human resource management strategies.This research contributes to a deeper understanding of the dynamics of the relationship between work commitment, work motivation, and the work environment with employee performance in the company CV. Agung Paper Klungkung.